2017
DOI: 10.1039/c6cc09876b
|View full text |Cite
|
Sign up to set email alerts
|

Inverted perovskite solar cells based on lithium-functionalized graphene oxide as an electron-transporting layer

Abstract: Perovskite solar cells with an inverted p-i-n architecture were constructed under ambient conditions by employing materials of lower cost than standard cells. Thus, graphene oxide was used as a hole transporting material and Li-modified graphene oxide as an electron transporting material, while Al was used as a counter electrode. A maximum solar conversion efficiency of 10.2% was achieved by adding a Ti-based sol on the top of the Li-modified graphene oxide layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…However, a major drawback of planar m-TiO 2 ETLs, which renders them unsuitable for application as PSCs, is that their interfacial charge extraction is insufficiently rapid. [10,11] This suggests that suitably shaping the architecture of ETLs may be an alternative approach to optimize the charge dynamics at the TiO 2 /perovskite hetero-interface to improve the performance of the PSCs. [7,8] To solve this problem, we previously modified planar TiO 2 ETLs with a thin PC 61 BM buffer layer, and found that the elastic nature of the PC 61 BM could facilitate the formation of high-quality perovskite films and improve the TiO 2 /perovskite interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a major drawback of planar m-TiO 2 ETLs, which renders them unsuitable for application as PSCs, is that their interfacial charge extraction is insufficiently rapid. [10,11] This suggests that suitably shaping the architecture of ETLs may be an alternative approach to optimize the charge dynamics at the TiO 2 /perovskite hetero-interface to improve the performance of the PSCs. [7,8] To solve this problem, we previously modified planar TiO 2 ETLs with a thin PC 61 BM buffer layer, and found that the elastic nature of the PC 61 BM could facilitate the formation of high-quality perovskite films and improve the TiO 2 /perovskite interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the modest efficiency of these solar cells and the high cost of the PC 61 BM, it is still essential as well as vital to explore a more comprehensive way to boost the charge extraction and performance of these solar cells. Enlarging the TiO 2 /perovskite interfacial area may effectively release the accumulated electrons at the hetero‐interface because this would increase the probability of electron extraction by the ETL . This suggests that suitably shaping the architecture of ETLs may be an alternative approach to optimize the charge dynamics at the TiO 2 /perovskite hetero‐interface to improve the performance of the PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the merits of broad and strong light absorption, long charge carrier diffusion length, bipolar transport properties, and longer carrier lifetime of the organometal halide perovskites, hole‐ and electron‐transporting layers also play essential role in improving the device performance of PSCs. According to the layer stacking sequence, planar heterojunction PSCs are divided into p–i–n (inverted) and n–i–p (normal) structures . Whatever the structure may be inverted PSCs or a normal PSCs, hole‐transporting materials (HTMs) undertake the responsibility of extracting and collecting the photon‐generated holes from the perovskite active layer .…”
Section: Introductionmentioning
confidence: 99%
“…Our concept was to replace the unstable organic components by constructing inverted PSCs with graphene derivatives (i.e., graphene oxide and lithium-functionalized graphene oxide as hole- and electron-transporting layers, respectively). 20,21 However, there are still other choices to make. Thus, in the present work, we have succeeded in constructing functional cells by completely eliminating organic hole transporters and by substituting them with a NiO x −GO blend.…”
Section: Introductionmentioning
confidence: 99%